(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ambarwati R, Rahayu DA, Rachmadiarti F, Khaleyla F. 2021. DNA barcoding of lamp shells (Brachiopoda: Lingula anatina) from Probolinggo, East Java, Indonesia. Biodiversitas 22: 1764-1774. Lingula anatina is one of brachiopods found in tropical regions, however, the reports on this species from South East Asia is currently limited. This study, therefore, aims to identify the Cytochrome Oxidase subunit I (COI) sequence and phylogenetic of lamp shells from Probolinggo, Indonesia. A total of five samples of lamp shells were collected from Probolinggo, Indonesia, then identified based on morphological characters, and the identification was confirmed using molecular data. Subsequently, molecular characterization and identification were conducted based on 657 bp of COI gene similarity, sequence variation, genetic distance, phylogenetic topology, and BOLD System. According to the results, the Lingula species found in Probolinggo Indonesia was Lingula anatina. The median-joining network and Automatic Barcode Gap Discovery (ABGD) analysis showed this Lingula anatina population from Probolinggo had relatives of 22 haplotypes and divided into six haplogroups. Furthermore, the population belonged to the same haplogroup but had different haplotypes. Thus, this study provides more information for Lingula anatina phylogenetic and haplotype studies.